Importance of Trees Outside Forest (TOF) for immediate earthquake response (Journal of Biodiversity Conservation and Bioresource Management, 2021)
A study was carried out in Thulosirubari village of Chautara Sangachowkgadi municipality of Sindhupalchok district, Nepal to analyse the importance of TOF for immediate earthquake response and recovery. More than 80% of the households have trees in their own land with species such as Chilaune (Schima wallichii), Kutmiro (Litsea monopetala), Khote Salla (Pinus roxburghii) and Bamboo are common. Among surveyed households (134), more than 75% respondents reported that they used Schima wallichii for pillar (Khaba) to make temporary houses, whereas bamboo was used for all kind of poles (Dada/Vata/Balo) in more than 80% of temporary houses. Both Bamboo and Schima wallichii were either extracted from their own land or from neighbour's land, i.e. TOF which were easily available and collected as required. We could not draw any statistical conclusion in choice of species to construct temporary houses by wealth categories. However, we have observed that people who have sufficient and varieties of trees in own land, have selected strong and hard wood for permanent house construction whereas those who do not have choice, are limited to use any of the available tree species. People were highly aware about importance of trees to cope with disaster; however selection of species was still debatable because of limited knowledge and researches.J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(1): 9-16